INTEGRASI NILAI-NILAI PENDIDIKAN MULTIKULTURAL DALAM PROSES PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN (PKn) DI SMP NEGERI 6 BANJARMASIN - Nur Fajrin (Jurnal Pendidikan Kewarganegaraan, 2014)
The integrationvalues ofmulticultural educationis an attemptto combine thelearning strategiesthat includesmulticultural valuesin acknowledging, accepting and affirminghumandifferences and similaritiesthat includediversityof race, language, religion, raceandgender. It is doneby developinginstructional designthatincludes planning, implementation, andevaluationof PKn which includingmulticultural values.LearningPKnasteaching materials isintegrated withthe values ofmulticultural educationin order toincrease the value ofequality, democraticvaluesandtolerancebetween people. In this study, the writer useda qualitative method. The data collectiontechniqueswere observation, interviews, anddocumentation. Moreover, the data analysis techniques used data reduction, data display, and conclusion.The resultsof this studywerein the process ofplanninglearningPKn whichincludedMulticulturalvaluesinSMPN6Banjarmasin: the teachersalreadyhad asyllabusfortheir teaching and learning process, the teacher also alreadyhad the Lesson Plan (RPP) which has been integratedwiththe values ofmulticultural educationintothe Lesson Plan and the teachers had more than one thematerials/textbook when teaching Pkn. On the other hand, theimplementation ofthe teaching and learning process of PKn whichincludingmulticulturalvaluesinSMPN6Banjarmasinhas been runningprettywellsince it had included:carrying out the pre-activities, carrying out the while-activities which includedconductingcorevalues of equality, democracyandtolerance and the lastwas carrying out the post-activities. Then, the teachers haveimplemented the principles ofassessment for the evaluation ofthe teaching andlearning process of PKn whichincludedmulticulturalvaluesinSMPN6Banjarmasin. The principles ofassessment were valid, objective, fair, unified, open, thoroughandcontinuous, systematic, based on thecriteria, andaccountable.According to the results, it is suggested thatthe PKn teachersatSMPN6Banjarmasinshould improve the integrationvalues ofmulticultural educationin the teaching and learning processof PKn, it was based on the fact that SMPN6Banjarmasinhavestudents who werediversein terms ofethnicity, culture, language, religion, socialstatus, gender, ability, ageandrace.Keywords: Integration, The Values of Multicultural Education, Teaching and Learning PKn.